(untitled) (Advancements in Homeopathic Research, 2022)
Squamous or seborrheic blepharitis is a common variety of anterior blepharitis where there is a chronic inflammatory condition of eyelids with deposition of scale at base of eyelashes leading to symptoms of itching, burning and redness of eyelid margin along with glaring of light with dryness of eyes. It usually occurs due to lack of hygiene,exposure to external irritants and endogenous factors such as allergies, septic focus, seborrhoeic dermatitis of scalp etc. Conventional treatment includes daily cleaning of eyelashes and topical use of antibiotic with steroids, however it gives only a temporary relief. Homoeopathy was found effective in treating different metabolic disorders when prescribed on the basis of symptom-similarity. A case reported was a female aged 34 years suffering from squamous blepharitis for 7 years and was prescribed modern medicines that gave temporarily relief but showed a recurrence after 2 years. Repetition of same treatment failed to give relief, so patient turned to homoeopathic treatment. Homoeopathic Natrium sulphuricum 30C prescribed on the basis of peculiar local symptoms, thermal state and miasm resolved her condition completely within 3 weeks. This case report shows effectiveness of individualized homoeopathy in squamous blepharitis.